Molecular cloning and expression analysis of C-type lectin (RpCTL) in Manila clam Ruditapes philippinarum after lipopolysaccharide challenge. Issue 86 (March 2019) - Li, Dongdong; Nie, Hongtao; Dong, Shasha; Huo, Zhongming; Yan, Xiwu
Abstract: The Manila clam, Ruditapes philippinarum, is one of the most commercially important marine bivalves. C-type lectins (CTLs) are pattern recognition receptors (PRRs) that play important roles in the identification and elimination of pathogens by the innate immune system. In this study, a new CTL (RpCTL) was identified in the Manila clam, R. philippinarum . The full-length RpCTL cDNA is 802 bp, with an open reading frame of 591 bp, encoding 196 amino acids, including an N-terminal signal peptide and a carbohydrate recognition domain (CRD). RpCTL contains conserved CRD disulfide bonds involving four cysteine residues (Cys 30 –Cys 104, Cys 124, and Cys 132 ), and the EPN (Glu 94 –Pro 95 –Asn 96 ) and WND (Trp 119 –Asn 120 –Asp 121 ) motifs. Quantitative reverse transcription (RT)–PCR detected RpCTL transcripts mainly in the gill, siphon, and hepatopancreas in three shell-color strains (zebra, white, and white–zebra strains) and two unselected populations of R. philippinarum, and the gene was highly expressed in the hepatopancreas after lipopolysaccharide treatment. Antimicrobial activity assays of recombinant RpCTL against both Gram-positive and Gram-negative bacteria showed that RpCTL inhibits microorganismal growth. In a survival test, RpCTL inhibited and killed Vibrio anguillarum in R. philippinarum . These results suggest that RpCTL participates in the pathogen identification process of R. philippinarum as a PRR and in its immune defense system. Highlights: Full length cDNA of RpCTL was cloned from the Manila clam by RACE method. The mRNA transcripts of RpCTL expressed at the highest level in hepatopancreas. Expression analysis of RpCTL was performed in clam after lipopolysaccharides (LPS) challenge.